Regulation, resource reallocation and productivity growth - Jens Arnold; Giuseppe Nicoletti; Stefano Scarpetta (EIB Papers, 2011)
In this paper, we review theory and evidence on the links between product market regulations that curb competitive pressures, the efficiency of resource allocation and productivity growth. We show that product market regulations differ across countries and industries and have evolved differently over time. We argue that differences in regulation have played an important role in driving resource allocation and productivity outcomes. Countries and industries where direct and indirect regulatory burdens are lighter have generally experienced the highest GDP per capita and productivity growth rates. Moreover, where regulatory burdens are lighter, the reallocation of resources towards the highest-productivity firms is stronger. The impacts of inappropriate regulations on aggregate and firm-level productivity performance are estimated to be quantitatively important and thus, reforming such regulations can provide a significant boost to potential growth in OECD economies.
Keywords: 330; Regulierung; Allokationseffizienz; Produktivität; Sozialprodukt; Wirtschaftswachstum; OECD-Staaten